Overexpression of the Peach Transcription Factor Early Bud-Break 1 Leads to More Branches in Poplar - Zhao, Xuehui; Wen, Binbin; Li, Chen; Tan, Qiuping; Liu, Li; Chen, Xiude; Li, Ling; Fu, Xiling (Frontiers in Plant Science, 2021)
Shoot branching is an important adaptive trait that determines plant architecture. In a previous study, the Early bud-break 1 (EBB1) gene in peach (Prunus persica var. nectarina) cultivar Zhongyou 4 was transformed into poplar (Populus trichocarpa). PpEBB1-oe poplar showed a more branched phenotype. To understand the potential mechanisms underlying the EBB1-mediated branching, transcriptomic and proteomics analyses were used. The results showed that a large number of differentially expressed genes (DEGs)/differentially expressed proteins (DEPs) associated with light response, sugars, brassinosteroids (BR), and nitrogen metabolism were significantly enriched in PpEBB1-oe poplar. In addition, contents of sugars, BR, and amino acids were measured. Results showed that PpEBB1 significantly promoted the accumulation of fructose, glucose, sucrose, trehalose, and starch. Contents of brassinolide (BL), castasterone (CS), and 6-deoxocathasterone (6-deoxoCS) were all significantly changed with overexpressing PpEBB1. Various types of amino acids were measured and four of them were significantly improved in PpEBB1-oe poplar, including aspartic acid (Asp), arginine (Arg), cysteine (Cys), and tryptohpan (Trp). Taken together, shoot branching is a process controlled by a complex regulatory network, and PpEBB1 may play important roles in this process through the coordinating multiple metabolic pathways involved in shoot branching, including light response, phytohormones, sugars, and nitrogen.